Learn Adobe Photoshop CS5 by video core training in visual communication (video sneak peek) - McCathran, Kelly (Video2brain, 2010)
"This innovative product from Adobe Press combines interactive video and a full-color printed reference to teach the fundamentals of Photoshop CS5 as well as the basic principles of graphic design. Structured around the objectives of the "Visual Communication using Adobe Photoshop CS5" exam at the Adobe Certified Associate level, this Adobe-approved product teaches how to edit images with precise selection control and create dramatic visual effects with Photoshop"--Resource description page.